Attitude towards Continuous Internal Assessment and Study Habits of the Student Teachers in Manipur - Devi, Kangjam Dijita; Devi , Chongtham Beda; Singh , Chongtham Khogendra (International Journal of Membrane Science and Technology, 2023)
The study's main purpose is to analyze the attitude towards CIA and study habits of B.Ed. student teachers and their relationship. A randomly drawn group of 600 B.Ed. student teachers enrolled at different teacher education colleges affiliated with Manipur University during the academic year 2023-24 responded to a set of self-administered questionnaires comprising Study Habits developed by Mukhopadhyay and Sansanwal (2015) and Attitude Towards Continuous Internal Assessment (CIA) developed by the researcher. For analysing and interpreting the test scores, percentage and Pearson’s Product Moment Coefficient of Correlation to see the relationship between the variables. All the statistical treatments have been done with IBM SPSS Statistics Version 22 software. The results revealed that the maximum number of B.Ed. student teachers fall under the category of moderate level of attitude, with 378 (63.00%). The maximum number of B.Ed. student teachers fall under the category of moderate study habits, with 233 (38.83%). Increases in B.Ed. student teachers’ study habit statuses were correlated with increases in their attitude towards continuous internal assessment. In conclusion, future research may investigate the joint and relative contribution of other demographic variables of student teachers to predict their attitudes toward continuous internal assessment practices.